2019
DOI: 10.1177/0300891619886657
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic CT findings of malignant bowel obstruction in patients with advanced ovarian cancer

Abstract: Objective: To evaluate computed tomography (CT) findings able to predict outcome in patients with ovarian cancer (OC) and concomitant bowel occlusion. Methods: This institutional review board–approved retrospective study included 31 patients with OC and clinical evidence of bowel occlusion who underwent CT at presentation between February 2013 and June 2015. Two radiologists recorded various qualitative CT features. Correlations between CT and survival data were made with Mann-Whitney test, Wilcoxon test, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The open operation [ 17 ] refers to etching first and then expanding, which can eliminate small areas with higher brightness, separate objects at slender points, etc., which is expressed as the following equation. …”
Section: Methodsmentioning
confidence: 99%
“…The open operation [ 17 ] refers to etching first and then expanding, which can eliminate small areas with higher brightness, separate objects at slender points, etc., which is expressed as the following equation. …”
Section: Methodsmentioning
confidence: 99%
“…We reviewed the clinical records of all consecutive patients with MBO due to PM who underwent palliative surgery. The diagnosis of MBO was established on clinical and CT-scan findings (10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“… 16–23 Moreover, a recent retrospective review identified CT findings of ascites, mesenteric disease, and dilated bowel loop wall thinning as poor prognostic indicators. 24 …”
Section: Diagnosis and Prognostic Factorsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Moreover, a recent retrospective review identified CT findings of ascites, mesenteric disease, and dilated bowel loop wall thinning as poor prognostic indicators. 24 Retrospective analyses have shown that systemic chemotherapy after the development of MBO is associated with superior survival, irrespective of whether patients were treated medically or surgically for MBO. [25][26][27] In advanced ovarian cancer, disease status is an important prognostic factor of treatment response and thus MBO outcome.…”
mentioning
confidence: 99%